ALAT PERAGA TANGGA PINTAR UNTUK MATERI PENGUKURAN PANJANG SISWA SEKOLAH DASAR - Indriani, Ari; Mayasari, Novi (Jurnal Riset Pembelajaran Matematika, 2023)
Grade 3 students at SD N 2 Kedungwaru still have difficulty understanding length measurement material. The purpose of this study was to determine students' understanding of the length measurement material with smart ladders. The subjects of this study were 17 students in class III. This type of research is descriptive qualitative research. Methods of data collection using interviews, tests and documentation. While the analysis used by using the percentage (%). With a KKM score of 75, the score above the KKM is 13 students with a percentage of 76.47%. Based on the results of interviews with students who have scores above the KKM, they say that learning with visual aids is more fun and can be practiced directly so that the material obtained is easier to understand and remember. And there are 4 students whose grades are below the KKM. Students whose grades are still below the KKM because students are still confused about whether the question is multiplied or divided up the ladder up or divided or vice versa whether the descending ladder is multiplied or divided. Learning mathematics in measurement material can use smart board teaching aids and these teaching aids can help elementary school students understand measurement material. Keywords: Smart board, length measurement